Factors Influencing Voluntary Enrollment in National Health Insurance Funds among Market Vendors: A Case of Mwanza, Tanzania - Mushi Laurell; Saronga Happiness; Temesgen Anjulo Ageru; Hien Thi Nguyen; Sanhawat Chaiwong; Francis Walugembe (My University, 2024)
The National Health Insurance Fund (NHIF) recently developed new affordable packages aimed at attracting enrolment of new clients into the health insurance scheme, however, NHIF still faces low enrollment of clients primarily from the informal sector. This study aims to understand the factors affecting the uptake of voluntary NHIF in the informal sector, focusing on how demographic factors, socioeconomic status, level of awareness, and perceived quality of health care affect the uptake of voluntary NHIF in the informal sector. Therefore, the aim of this study was to determine factors influencing voluntary uptake of NHIF among market vendors in Mwanza. Method: The study design was cross-sectional descriptive to establish factors associated with the uptake of NHIF in the informal sector. The factors explored were socio-demographic, economic, NHIF awareness and perception of health care quality. Data were collected using structured questionnaires. The respondents were from two municipal city markets in Mwanza. Data was analyzed using SPSS version 26.0 software. Descriptive analysis was performed for the background characteristics of respondents, awareness, and perception. Chi-square was used to determine factors associated with NHIF uptake. Results Data were collected from 323 market vendors from two municipal markets of Mwanza. Main source of income, perception, and awareness were positively associated with NHIF enrollment. The odds of enrolling in NHIF among respondents with low NHIF awareness were 92% lower than among respondents with high NHIF awareness. The odds of enrolling in NHIF among respondents with negative perceptions on the quality of health care services was 83% lower than among respondents with positive perceptions. Conclusion: NHIF uptake among market vendors in Mwanza City was still low. The study reports that source of income, poor awareness of the fund by the respondents, and negative perceptions with regard to quality of health care negatively affect enrollment in NHIF. The study recommends using information, education, and communication strategies to raise awareness of NHIF and create demand for insurance in the informal sector. Moreover, a review of the affordability of NHIF packages in relation to the income earned by the majority in the informal sector is important to attract enrollment.
This manuscript examines the factors influencing voluntary enrollment in National Health Insurance Funds (NHIF) among market vendors in Mwanza, Tanzania. With the growing importance of health insurance coverage in low-income settings, understanding the barriers and motivators for enrollment is crucial for improving coverage and ensuring sustainable health systems. The study investigates socio-economic, demographic, and awareness-related factors that impact the willingness of market vendors to join the NHIF. Data was collected through a mixed-methods approach, combining surveys and interviews, to provide both quantitative insights and qualitative understanding of the decision-making process. The findings offer valuable implications for policy-makers and health practitioners, aiming to enhance the uptake of health insurance among informal sector workers and marginalized groups. This research contributes to the ongoing dialogue on universal health coverage in Tanzania and similar settings in Sub-Saharan Africa.
Keywords: National insurance; Tanzania